Improved retention of patients starting antiretroviral treatment in Karonga District, northern Malawi, 2005-2012 - Koole, Olivier (J Acquir Immune Defic Syndr, 2014)
BACKGROUND: Patient retention in antiretroviral therapy (ART) programs remains a major challenge in sub-Saharan Africa. We examined whether and why retention in ART care has changed with increasing access. METHODS: Retrospective cohort study combining individual data from ART registers and interview data, enabling us to link patients across different ART clinics in Karonga District, Malawi. We recorded information on all adults (≥15 years) starting ART between July 2005 and August 2012, including those initiating due to pregnancy and breastfeeding (Option B+). Retention in care was defined as being alive and receiving ART at the end of study. Predictors of attrition were assessed using a multi-variable Cox-proportional hazards model. RESULTS: The number of clinics providing ART increased from one in 2005 to 16 in 2012. Six month retention increased from 73% (95%CI 71-76) to 93% (92-94) when comparing the 2005-06 and 2011-12 cohorts, and 12-month retention increased from 70% (67-73) to 92% (90-93). Over the study period, the proportion of patients starting ART at WHO stage 4 declined from 62% to 10%. Being a man, younger than 35 years, having a more advanced WHO stage and being part of an earlier cohort were all independently associated with attrition. Women starting ART for Option B+ experienced higher attrition than women of child-bearing age starting for other reasons. CONCLUSIONS: In this area retention in care has increased dramatically. Improved health in patients starting ART and decentralization of ART care to peripheral health centres appear to be the major drivers for this change.